Drug‐delivering nerve conduit improves regeneration in a critical‐sized gap. Issue 1 (27th October 2018) - Labroo, Pratima; Hilgart, David; Davis, Brett; Lambert, Christopher; Sant, Himanshu; Gale, Bruce; Shea, Jill E.; Agarwal, Jayant
Abstract: Autologous nerve grafts are the current "gold standard" for repairing large nerve gaps. However, they cause morbidity at the donor nerve site and only a limited amount of nerve can be harvested. Nerve conduits are a promising alternative to autografts and can act as guidance cues for the regenerating axons, without the need to harvest donor nerve. Separately, it has been shown that localized delivery of GDNF can enhance axon growth and motor recovery. FK506, an FDA approved small molecule, has also been shown to enhance peripheral nerve regeneration. This paper describes the design of a novel hole‐based drug delivery apparatus integrated with a polytetrafluoroethylene (PTFE) nerve conduit for controlled local delivery of a protein such as GDNF or a small molecule such as FK506. The PTFE devices were tested in a diffusion chamber, and the bioactivity of the released media was evaluated by measuring neurite growth of dorsal root ganglions (DRGs) exposed to the released drugs. The drug delivering nerve guide was able to release bioactive concentrations of FK506 or GDNF. Following these tests, optimized drug releasing nerve conduits were implanted across 10 mm sciatic nerve gaps in a BL6 yellow fluorescent protein (YFP) mouse model, where they demonstrated significant improvement in muscle mass, compound muscle action potential, and axon myelination in vivo as compared with nerve conduits without the drug. The drug delivery nerve guide could release drug for extended periods of time and enhance axon growth in vitro and in vivo. Abstract : This paper describes the design of a novel drug delivery apparatus integrated with a PTFE (polytetrafluoroethylene) based nerve conduit for controlled local delivery of a protein such as GDNF or a small molecule such as FK506.